IMPROVED UNDERSTANDING OF PARENTS IN THE USE OF SOCIAL MEDIA INTELLIGENTLY AND WISELY IN POSBINDU MELATI PUTIH: PENINGKATAN PEMAHAMAN ORANG TUA DALAM PENGGUNAAN MEDIA SOSIAL SECARA CERDAS DAN BIJAK DI POSBINDU MELATI PUTIH - Dede Handayani; Edi Mariyanto; Khanif Faozi; Oke Hariansyah; Wiwin Winarti (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2022)
The purpose of this Community Service activity is to educate and provide knowledge to parents on how their children can use social media intelligently and wisely. The method used in this community service activity involves, firstly, lectures using power point slides to explain to the participants. General knowledge about how to assist in utilizing social media, as well as sharing experiences through discussions and question and answer sessions. This community service resulted in increased knowledge and understanding of participants, namely housewives or parents regarding the wise and intelligent use of social media in everyday life. Based on the results of the pretest and posttest, the socialization carried out can increase understanding of Increasing Parents' Understanding of Using Social Media Smartly and Wisely at Posbindu Melati Putih